Dissemination of Disaster Preparedness Schools (SSB) in Pariaman City - Dedi Hermon; Erianjoni Erianjoni; Aprizon Putra (Science and Environmental Journal for Postgraduate, 2021)
Community service activities with this type of Community Partnership Program (PKM) are carried out as a form of higher education participation (Department of Geography, Faculty of Social Sciences – Padang State University/FIS-UNP) in Middle Schools First (SMP) in Pariaman City by taking into account the various conditions experienced by students and the school in the school. The complexity of these problems can have an impact that can affect teaching and learning activities in SMP coastal regions of Pariaman City, such as SMP 1 (Kampung Perak, Central Pariaman), SMP 2 (Kampung Baru, Central Pariaman), SMP 4 (Rawang, Central Pariaman), and SMP 7 (Manggung, North Pariaman). then the PKM program team to the SMP scope schools through the Education, Youth, and Sports (PPO) Office in Pariaman City from the Department of Geography FIS-UNP intend to provide information and practical knowledge to students and schools related to disaster risk management that can be done if at any time a disaster occurs so that a disaster preparedness school is realized in Pariaman City The purpose of community service activities PKM is to instill awareness in students, schools and the community about the importance of early vigilance and preparedness to reduce the risk of disasters that cause loss of life and property thing. This PKM program is focused on junior high school students in the coastal region of ​​Pariaman City through socialization activities for disaster preparedness schools (SSB) and training in earthquake disaster management with the potential for a tsunami. The method used in this service activity is to use an andragogy approach. This approach is used to optimize participant participation in each planned activity agenda, and a simulation training approach using several signs in the concept of earthquake disaster mitigation with the potential for a tsunami, such as evacuation routes, evacuation points, and gathering points that have previously been prepared in the form of structured research. . Partners in this PKM program include the head of the PPO Office, and the school (principals, teachers, students, staff, and school guards) and the surrounding community. The expected result of this activity is the dissemination of various information related to earthquake disaster mitigation measures with the potential for a tsunami with various supporting aspects, such as 1) the formation of a disaster preparedness school community at the junior high school level in Pariaman City; 2) availability of data and information in the form of earthquake and tsunami disaster risk management maps in Pariaman City; and 3) scientific publications in the form of accredited national journals.